Factors controlling the past ~150-year ecological dynamics of Lake Wuliangsu in the upper reaches of the Yellow River, China. (September 2015) - He, Yuxin; Sun, Dayang; Wu, Jinglu; Sun, Yongge
Lacustrine ecosystem history since the industrial revolution provides important evidence of natural versus anthropogenic effects on the environment. With high-resolution sedimentary core samples and organic–inorganic geochemical methods, we reconstruct the past ~150-year ecosystem evolution of Lake Wuliangsu in the upper reaches of the Yellow River, and probe factors controlling the ecological dynamics. In this study, ecological changes in Lake Wuliangsu over the past ~150 years were identified. After the lake formed in the 1850s, biological productivity of the lake was still under-developed until the 1950s. During the period of 1950s–1970s, submerged macrophytes became the dominant organisms in the lake because of lake area expansion and slight increases of nutrient input from agricultural development in the catchment. The domination of submerged macrophytes ceased after the 1970s, which was possibly induced by the shrinkage of the lake area. After the 1990s, the main contributor of sedimentary n -alkanes most likely shifted to reeds because of eutrophication caused by anthropogenic activities. The results clearly demonstrate that the ecosystem in Lake Wuliangsu before the 1950s strongly depended on the natural discharge, whereas at later stages, it was significantly influenced by human activities. During the period of 1950s–1990s, the human-monitored lake area seems to be the main factor in the lake ecosystem evolution. However, when the nutrient supply went beyond the tipping point after the 1990s, eutrophication took over and played a key role in the lake ecosystem evolution.